Disease and Disapproval: COVID-19 Concern is Related to Greater Moral Condemnation. (10th June 2021) - Henderson, Robert K.; Schnall, Simone
Prior research has indicated that disease threat and disgust are associated with harsher moral condemnation. We investigated the role of a specific, highly salient health concern, namely the spread of the coronavirus, and associated COVID-19 disease, on moral disapproval. We hypothesized that individuals who report greater subjective worry about COVID-19 would be more sensitive to moral transgressions. Across three studies ( N = 913), conducted March-May 2020 as the pandemic started to unfold in the United States, we found that individuals who were worried about contracting the infectious disease made harsher moral judgments than those who were relatively less worried. This effect was not restricted to transgressions involving purity, but extended to transgressions involving harm, fairness, authority, and loyalty, and remained when controlling for political orientation. Furthermore, for Studies 1 and 2 the effect also was robust when taking into account the contamination subscale of the Disgust Scale–Revised. These findings add to the growing literature that concrete threats to health can play a role in abstract moral considerations, supporting the notion that judgments of wrongdoing are not based on rational thought alone.